Contemporary Craft in Iceland: Communicating - Hawson, Thomas (2006)
This doctoral project develops an interdisciplinary collaborative approach to furniture designer\maker practice. At its core is a practice-based framework that can be used to assess and reflect upon the tacit, primarily visual nature of makers’ knowledge and the way that this can be communicated in order to develop design outcomes. The enquiry takes as its focus a two-year collaboration between the author – a British-based furniture designer/maker – and six indigenous Icelandic craft practitioners in which the ultimate goal was the creation of artefacts that, it was hoped, would be expressive of Iceland’s native craft traditions. During the ‘Iceland Project,’ as it came to be known, interaction between and among participants was grounded in a predetermined plan developed democratically through consultation and dialogue. The project successfully develops new knowledge through a contemporary reinterpretation of indigenous Icelandic craft-making knowledge and demonstrates this through the making of artefacts imbued with recognized cultural status. It also extends furniture designer/maker research by developing an innovative practice-based method of collaboration rooted in the multimedia archiving of the making process which can then be used to illuminate and facilitate future practice. The project is a scholarly display of makers’ knowledge: the process is shared democratically among peers; the decisions that articulate design and methods of making are reviewed; and inter-subjective outcomes are generated. To facilitate learning from designer/maker practice-based research, the creative narrative is necessarily partly articulated through visual media and artifacts.